In vivo wound healing and antiulcer properties of white sweet potato (Ipomoea batatas) - Hermes, Daniele; Dudek, Débora N.; Maria, Mariana D.; Horta, Lívia P.; Lima, Eliete N.; de Fátima, Ângelo; Sanches, Andréia C.C.; Modolo, Luzia V. (Journal of advanced research, 2013)
The potential of tuber flour of Ipomoea batatas (L.) Lam. cv. Brazlândia Branca (white sweet potato) as wound healing and antiulcerogenic agent was investigated in vivo in animal model. Excision on the back of Wistar rats was performed to induce wounds that were topically treated with Beeler’s base containing tuber flour of white sweet potato at 2.5%. Number of cells undergoing metaphase and the degree of tissue re-epithelialization were investigated 4, 7 and 10days post-treatment. The protective effect of aqueous suspension of tuber flour (75 and 100mg/kg animal weight) on gastric mucosa of Wistar rats was also studied by using the ethanol-induced ulceration model. Ointment based on white sweet potato at 2.5% effectively triggered the healing of cutaneous wound as attested by the increased number of cells undergoing metaphase and tissue re-epithelialization regardless the time of wound treatment. Tuber flour potentially prevented ethanol-induced gastric ulceration by suppressing edema formation and partly protecting gastric mucosa wrinkles. Crude extracts also exhibited potential as free radical scavengers. The results from animal model experiments indicate the potential of tuber flour of white sweet potato to heal wounds.